Not just little adults: preparing a children's emergency department for COVID-19. Issue 8 (1st July 2020) - Adamson, Jonathan; Bird, Chris; Edgworth, Kate; Hartshorn, Stuart; Jamalapuram, Kasyap; Kanani, Anand; Mackay, Kate; Newton, Tina; Stanhope, Ben; Wilson, Bridget
Abstract : COVID-19 presented unique challenges in preparing our stand-alone children's emergency department for the pandemic and has demonstrated well the paediatric adage, 'children aren't little adults'.